Electroencefalografía en Caninos (2019)
The frequency of seizures in canines fluctuates from 0.5% to 5.7% of consultations at the small animal clinic, where 80% are caused mainly due to idiopathic epilepsy (Goiz, 2008) which has been of interest, and object of study as recorded in the literature (Thomas, 2010) (Ekenstedt, 2013), due to the increase in queries for this reason.